Perencanaan lanskap Pantai Sidayu sebagai waterfront park Kabupaten Klungkung, Bali - Ida Bagus Kartadipa; I Gusti Agung Ayu Rai Asmiwyati; Ida Ayu Mayun (Prodi Arsitektur Lanskap, Fakultas Pertanian, Universitas Udayana, 2025)
Klungkung Regency is one of the districts in Bali which has many beaches that have the potential to be used as recreational areas. One beach is called Sidayu located in the southern part of Klungkung Regency. According to regional regulations, this beach is an area that can be potentially developed into a recreational area as it offers a beautiful vast rice field and ocean view. However, from observations, this beach has not yet plan well. There was no inadequate space arrangement and facilities to support recreational activities. This research aims to develop this beach into a recreational area by applying the waterfront park concept according to waterfront principles. The research method used is a qualitative descriptive method with data collection techniques including observation, interviews, and literature study. The research stages consist of inventory, analysis, synthesis, and concepts with the aspects studied being biophysical and socio-cultural aspects. There were two zones recommended, namely the active recreation zone without which is an undeveloped zone, and the passive recreation zone for development infrastructure. The circulation plan was divided into primary circulation, secondary circulation, and alternative assistance routes. The vegetation plan provided was carried out by maintaining the original vegetation and adding new vegetation according to its function and character. Part of the facility concept is the concept of supporting facilities and coastal protection infrastructure facilities. The product resulting from the research carried out is in the form of a recommended image of Sidayu Beach as a recreation park in the form of a site plan